PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS KERJA PADA KARYAWAN PT TUNAS BATAM KARYA - Arini, Dessy Wida; Herman, Hendri (SCIENTIA JOURNAL, 2019)
The current industrial development in Indonesia is very tight. The aim of this study was to determine the effect of leadership style, work motivation and organizational culture on the work productivity of PT Tunas Batam Karya employees both partially and simultaneously. The sample used was 104 employees of PT Tunas Batam Karya. This type of research is quantitative research. Quantitative analysis includes validity test, reliability test, classical assumption test, multiple linear analysis test, determination coefficient test (R2), t-test and f-test. Data from this study were processed with SPSS version 21. The results of this study have a partial leadership style that has a positive and significant influence on labor productivity, work motivation has a positive and significant influence on labor productivity and the organizational culture has a positive and significant effect work on labor productivity. While simultaneous results, leadership style, work motivation and organizational culture have a significant and significant impact on the productivity of the workforce of PT Tunas Batam Karya employees. What has been done What has not been done in software development will be discussed at the end of this thesis.